2009
DOI: 10.1108/02640470910947593
|View full text |Cite
|
Sign up to set email alerts
|

From information commons to knowledge commons

Abstract: PurposeBased on the information commons service model, the aim of this article is to propose a new model for knowledge commons. It seeks to define the conceptual model and constructing framework of knowledge commons, which aim for a collaborative knowledge‐sharing environment to support innovative community activities of university library.Design/methodology/approachBy analyzing the innovation activities of communities, infusing theories of knowledge management, collaboration and Library 2.0, the knowledge com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 12 publications
0
10
0
1
Order By: Relevance
“…In a Commons, knowledge is considered to be a shared resource to be enriched and maintained (Coriat, 2011). For example, communities combine their resources to provide public libraries (Shuhuai, Chen, Xingjun, Haiqing, & Jialin, 2009). The scientific community 'stands on the shoulders of giants' as it makes advances in complex problems that no person or organization could solve alone (Spier, 2002).…”
Section: Governing Open Source Communitiesmentioning
confidence: 99%
“…In a Commons, knowledge is considered to be a shared resource to be enriched and maintained (Coriat, 2011). For example, communities combine their resources to provide public libraries (Shuhuai, Chen, Xingjun, Haiqing, & Jialin, 2009). The scientific community 'stands on the shoulders of giants' as it makes advances in complex problems that no person or organization could solve alone (Spier, 2002).…”
Section: Governing Open Source Communitiesmentioning
confidence: 99%
“…The Knowledge Management Coordination Module is based on various authors (Porumbeanu, 2009;Castro, 2005;Shuhuai et al, 2009;Pacheco et al, 2005) and in the principles of institutional and management/administration effectiveness from the Association of College and Research Libraries (2011), as shown in Figure 6. Coordination of Knowledge Management includes everything that constitute the organization's knowledge strategy.…”
Section: Knowledge Management Coordination Modulementioning
confidence: 99%
“…The creation of a knowledge manager post such as a "Chief Knowledge Officer" greatly increases the chances of successful implementation of this new resource in libraries and information services (Porumbeanu, 2009). The knowledge management coordination module is based on various authors (Porumbeanu, 2009;Castro, 2005;Shuhuai et al, 2009;Pacheco et al, 2005) and in the principles of institutional and management/administration effectiveness from the Association of College and Research Libraries (2011), as shown in Figure 6.…”
Section: Knowledge Management Coordination Modulementioning
confidence: 99%
See 2 more Smart Citations